A Study of Accountability in Two Organizational Learning Frameworks: Why Accountability for Learning is Critical. Issue 3 (16th March 2017) - Baxter, David; Colledge, Thomas; Turner, Neil
Abstract : In this paper we examine the complex relationship between accountability and organizational learning through a case study with the UK Royal Air Force (RAF). Accountability is a complex and contradictory construct that has both positive and negative implications for organizational learning. Within the same organization we observed positive effects of accountability in one organizational learning system, and negative effects of accountability in another. This case study adds to the organizational learning and accountability literatures, showing that accountability to hierarchy, rather than preventing learning, can actually promote effective learning, making it more likely that people will report problems quickly and accurately and take follow‐up action. This only applies if the learning objectives align with the broader accountability framework, and if reporting on failures will enhance individual reputation. If not, then people will tend to avoid reporting negative events in order to avoid punishment and reputation damage. Accountability to hierarchy is only negative if it conflicts with the learning objectives.